Building with no end in sight: the theory and effects of prison architecture. Issue 3 (26th May 2020) - Nadel, Melissa R.; Mears, Daniel P.
ABSTRACT: The rise of mass incarceration necessitated increased investment in prisons. This increase occurred alongside of policy maker calls for greater government accountability and reliance on evidence-based practices. Despite advances in the understanding of "what works" to reduce crime and recidivism, a notable gap in research exists: What is the evidence that prison architecture influences inmate behavior or reentry outcomes? This article seeks to address that gap and argues that (1) prisons are designed to achieve specific goals, (2) there is minimal empirical evidence that variation in architecture achieves these goals, and (3) the theory by which architecture achieves these goals is inconsistent and unclear. Implications of this assessment for research, theory, and policy are discussed.